1984
DOI: 10.1111/j.1600-0765.1984.tb01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease in the domestic cat

Abstract: One hundred and fifty teeth from 15 cats of an average age of 6.8 years were examined macroscopically, radiographically, and histologically. Clinical inspection revealed plaque and calculus deposits on the facial surfaces of maxillary and mandibular premolars and molars. Radiography showed horizontal and vertical loss of alveolar bone with irregular defects of the dental hard structures. Histologically, typical features of gingival and periodontal destruction were found and resorptive lacunae were seen at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 19 publications
7
49
0
5
Order By: Relevance
“…Cementum formation beyond physiologic deposition is called hypercementosis and can commonly be observed in teeth of cats with FORL [12]. In one study, hypercementosis was demonstrated in all investigated feline teeth [14]. Excessive amounts of cellular cementum are deposited particularly at apical and midroot surfaces, sometimes causing bulbous root apices (Fig.…”
Section: Peculiarities Of Feline Permanent Teethmentioning
confidence: 99%
See 2 more Smart Citations
“…Cementum formation beyond physiologic deposition is called hypercementosis and can commonly be observed in teeth of cats with FORL [12]. In one study, hypercementosis was demonstrated in all investigated feline teeth [14]. Excessive amounts of cellular cementum are deposited particularly at apical and midroot surfaces, sometimes causing bulbous root apices (Fig.…”
Section: Peculiarities Of Feline Permanent Teethmentioning
confidence: 99%
“…Spontaneously repaired defects of cementum and superficial dentin are called surface resorptions, in which the anatomic contour of the root surface is restored [17]. Most clinically evident FORL appear histologically to be in resorptive and reparative phases simultaneously [14]. Although attempts at repair can be noted by production of bone, cellular cementum, and bonecementum [12][13][14]19,20,23], tooth resorption in cats is usually progressive Fig.…”
Section: Histologic and Radiographic Features Of Feline Odontoclasticmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of periodontal disease progression has been widely studied in horses, donkeys, cattle, dogs and cats, with artificial studies leading to further understanding the intricate workings of mobility, recession and bone resorption (Ericsson and Lindhe, 1982, Hamp et al, 1984, Lindhe et al, 1975, Lindhe and Svanberg, 1974, Sorensen et al, 1980, Clarke and Cameron, 1998, Dobereiner et al, 2000, du Toit and Dixon, 2011, Mallonee et al, 1988, Reichart et al, 1984, Dixon et al, 2000b.…”
Section: 2mentioning
confidence: 99%
“…La enfermedad periodontal es la afección oral más común en el perro adulto (Reichart et al, 1984;Colmery y Frost, 1986), y es causada por la acumulación de placa dental bacteriana en las superficies dentales, la cual induce una respuesta inflamatoria que desarrolla la gingivitis como primera etapa (Genco, 1984), y continúa hasta establecerse la periodontitis, donde, además de la gingivitis, hay una pérdida del tejido de soporte (ligamento periodontal y proceso alveolar) (Colmery y Frost, 1986). Se tiene evidencia que la salud sistémica de los perros se ve afectada con enfermedad periodontal, incluyendo afecciones renales y hepáticas (De Bowes, 2002), así como alteraciones cardiovasculares (Pavlica et al, 1998).…”
Section: Introductionunclassified